2015
DOI: 10.1557/jmr.2015.358
|View full text |Cite
|
Sign up to set email alerts
|

Laser metal deposition additive manufacturing of TiC/Inconel 625 nanocomposites: Relation of densification, microstructures and performance

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 38 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Pereira et al (2017), in the remelting evaluation applied in the misorietated volume reduction for turbine blades, they highlight similar behavior, as well as in the work, of similar objective, presented by Rottwinkel et al (2017). Cao and Gu (2015), when evaluating density ratio, microstructures, and performance of TiC / Inconel 625 nanocomposites deposited via LMD, they observed that when increasing the energy, operating temperature is high enough to increase melt pool temperature and reduce the liquid viscosity, improving wettability. In this way, remelting process was able to encompass the layer's entire thickness.…”
Section: Microhardness Test and Pin-on-disk Tribological Test In Dry Mediummentioning
confidence: 74%
“…Pereira et al (2017), in the remelting evaluation applied in the misorietated volume reduction for turbine blades, they highlight similar behavior, as well as in the work, of similar objective, presented by Rottwinkel et al (2017). Cao and Gu (2015), when evaluating density ratio, microstructures, and performance of TiC / Inconel 625 nanocomposites deposited via LMD, they observed that when increasing the energy, operating temperature is high enough to increase melt pool temperature and reduce the liquid viscosity, improving wettability. In this way, remelting process was able to encompass the layer's entire thickness.…”
Section: Microhardness Test and Pin-on-disk Tribological Test In Dry Mediummentioning
confidence: 74%
“…Therefore, a larger degree of undercooling of the melt resulting from an increased cooling rate and a lower actual crystallization temperature facilitates the formation of the welldeveloped secondary dendritic arms of columnar dendrites. In addition, the refinement of columnar dendrite which is defined by the dendrite spacing can be explained by [28,29] d ¼ bðv c Þ À1=3…”
Section: Resultsmentioning
confidence: 99%
“…Bakkar et al [ 27 ] investigated the high volume percent TiC reinforced (25–70%) Inconel 625 composites. Cao and Gu [ 28 ] investigated the microstructure and properties of Inconel 625 matrix composite coatings with 2.5 wt.% TiC nano-particles. The previously conducted researches in this field [ 24 , 25 , 26 , 27 , 28 ] show that nickel-based superalloys composite coatings reinforced by 2.5–50% TiC particles are characterized by 10–45% higher hardness and up to 6% higher wear resistance than metallic nickel-based superalloys coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Cao and Gu [ 28 ] investigated the microstructure and properties of Inconel 625 matrix composite coatings with 2.5 wt.% TiC nano-particles. The previously conducted researches in this field [ 24 , 25 , 26 , 27 , 28 ] show that nickel-based superalloys composite coatings reinforced by 2.5–50% TiC particles are characterized by 10–45% higher hardness and up to 6% higher wear resistance than metallic nickel-based superalloys coatings. The results [ 27 ] also show that the increased TiC particles content of 50–70% may cause defects in the microstructure due to lack of matrix penetration.…”
Section: Introductionmentioning
confidence: 99%